Revision der europäischen Aulacidae (Hymenoptera - Evanioidea). - Oehlke, Joachim (Contributions to Entomology = Beiträge zur Entomologie, 1983)
A determination of the species of this family had formerly not been possible because publications had remained widely unknown and the nomenclatural interpretations differend. On the basis of the examination of the types, the designation of lectotypes and the description of two hitherto unknown sexes, nine species are established foe Europe and keys to these parasitic wasps that are all rare are given. Nomenclatural Acts gibbator (Thunberg, 1822) (Pristaulacus), Lectotype described as Ichneumon gibbator gloriator (Fabricius, 1804) (Pristaulacus), Lectotype described as Bassus gloriator